Discovery, characterization and potential roles of a novel NF-YAx splice variant in human neuroblastoma - Cappabianca, Lucia; Farina, Antonietta Rosella; Di Marcotullio, Lucia; Infante, Paola; De Simone, Daniele; Sebastiano, Michela; Mackay, Andrew Reay (Journal of experimental & clinical cancer research, 2019)
Identification of novel cancer-associated splice variants is of potential diagnostic, prognostic and therapeutic importance. NF-Y transcription factor is comprised of NF-YA, NF-YB and NF-YC subunits, binds inverted CCAAT-boxes in ≈70% of gene promoters, regulates > 1000 cancer-associated genes and proteins involved in proliferation, staminality, differentiation, apoptosis, metabolism and is subject to component alternative splicing. RT-PCR evaluation of alternative NF-YA splicing in primary human neuroblastomas (NBs), led to discovery of a novel NF-YAx splice variant, also expressed during mouse embryo development and induced by doxorubicin in NB cells. Here, we report the discovery and characterisation of NF-YAx and discus its potential roles in NB. NF-YAx cDNA was RT-PCR-cloned from a stage 3 NB (provided by the Italian Association of Haematology and Paediatric Oncology, Genova, IT), sequenced and expressed as a protein using standard methods and compared to known fully-spliced NF-YAl and exon B-skipped NF-YAs isoforms in: EMSAs for capacity to form NF-Y complexes; by co-transfection, co-immunoprecipitation and Western blotting for capacity to bind Sp1; by IF for localisation; in AO/EtBr cell-death and colony formation assays for relative cytotoxicity, and by siRNA knockdown, use of inhibitors and Western blotting for potential mechanisms of action. Stable SH-SY5Y transfectants of all three NF-YA isoforms were also propagated and compared by RT-PCR and Western blotting for differences in cell-death and stem cell (SC)-associated gene expression, in cell-death assays for sensitivity to doxorubicin and in in vitro proliferation, substrate-independent growth and in vivo tumour xenograft assays for differences in growth and tumourigenic capacity. NF-YAx was characterized as a novel variant with NF-YA exons B, D and partial F skipping, detected in 20% of NF-YA positive NBs, was the exclusive isoform in a stage 3 NB, expressed in mouse stage E11.5-14 embryos and induced by doxorubicin in SH-SY5Y NB cells. The NF-YAx protein exhibited nuclear localisation, competed with other isoforms in CCAAT box-binding NF-Y complexes but, in contrast to other isoforms, did not bind Sp1. NF-YAx expression in neural-related progenitor and NB cells repressed Bmi1 expression, induced KIF1Bβ expression and promoted KIF1Bβ-dependent necroptosis but in NB cells also selected tumourigenic, doxorubicin-resistant, CSC-like sub-populations, resistant to NF-YAx cytotoxicity. The discovery of NF-YAx in NBs, its expression in mouse embryos and induction by doxorubicin in NB cells, unveils a novel NF-YA splice mechanism and variant, regulated by and involved in development, genotoxic-stress and NB. NF-YAx substitution of other isoforms in NF-Y complexes and loss of capacity to bind Sp1, characterises this novel isoform as a functional modifier of NF-Y and its promotion of KIF1Bβ-dependent neural-lineage progenitor and NB cell necroptosis, association with doxorubicin-induced necroptosis and expression in mouse embryos coinciding with KIF1Bβ-dependent sympathetic neuroblast-culling, confirm a cytotoxic function and potential role in suppressing NB initiation. On the other hand, the in vitro selection of CSC-like NB subpopulations resistant to NF-YAx cytotoxicity not only helps to explain high-level exclusive NF-YAx expression in a stage 3 NB but also supports a role for NF-YAx in disease progression and identifies a potential doxorubicin-inducible mechanism for post-therapeutic relapse.